A hard carbon material and its preparation method and application
Through pre -oxidation treatment and high -temperature carbonization of asphalt, prepare hard carbon materials with high first effect and high -charging discharge capacity, solve the problem of poor sodium sodium storage sodium sodium battery, and realize the efficient sodium storage and low of sodium ion batteries. Cost production.
Patent Information
- Application Number
- CN202211548671.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-05
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2042-12-05
AI Technical Summary
Due to the slow diffusion of sodium ions and the rapid changes in the electrode material volume, sodium storage performance is poor and it is difficult to obtain good electrochemical performance.
By pre -oxidation treatment under specific temperature and pressure, and high -temperature carbonization, it is prepared to prepare hard carbon materials with high first effect and high charge discharge capacity.
It improves the first efficiency and charging capacity of hard carbon materials, suitable for the negative electrode material of sodium ion batteries, and achieves high efficiency and low -production costs of sodium storage.
Smart Images

Figure CN115959647B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of sodium ion batteries, and in particular to a hard carbon material and a preparation method and application thereof; more particularly, to a preparation method of a hard carbon material, a hard carbon material, a negative electrode material and a sodium ion battery. Background Art
[0002] Lithium-ion batteries are a widely used electrochemical energy storage device in today's society. With the development of new energy vehicles, portable electronic devices and large-scale energy storage technology, the demand for them is increasing day by day, which also drives the increase in demand for lithium.
[0003] Sodium-ion battery technology is expected to replace lithium-ion batteries in many fields such as new energy vehicles and energy storage grids due to its advantages such as lower cost and higher safety. It is a promising battery technology. At the same time, sodium-ion batteries have the characteristics of low cost, high safety performance, and wide operating temperature range. They can be widely used in low-speed electric vehicles, renewable energy access, and 5G communication base stations.
[0004] However, sodium-ion batteries also have some technical bottlenecks. Due to their large atomic radius and large relative atomic mass, sodium ions diffuse slowly during battery charging and discharging, and the existing electrode materials have drastic volume changes and poor sodium storage performance, making it difficult to obtain good electrochemical performance.
[0005] Therefore, developing negative electrode materials that are more efficient in sodium storage and cheaper and more stable is a key step towards the large-scale application of sodium-ion batteries.
[0006] In view of this, the present invention is proposed. Summary of the invention
[0007] The first object of the present invention is to provide a method for preparing a hard carbon material, by pre-oxidizing asphalt at a specific temperature and a specific pressure, so that the prepared hard carbon material has a high initial efficiency and a high charge and discharge capacity.
[0008] The second object of the present invention is to provide a hard carbon material having the advantages of low cost, high initial efficiency and high charge and discharge capacity.
[0009] The third object of the present invention is to provide a negative electrode material.
[0010] A fourth object of the present invention is to provide a sodium ion battery having high sodium storage efficiency, high initial efficiency and high charge and discharge capacity, and low preparation cost.
[0011] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:
[0012] The present invention provides a method for preparing a hard carbon material, comprising the following steps:
[0013] The asphalt is pre-oxidized at a pressure of 5 to 50 bar and a temperature of 250 to 400° C. to obtain a pre-oxidized asphalt material;
[0014] The pre-oxidized asphalt material is carbonized at high temperature to obtain the hard carbon material.
[0015] Preferably, the pre-oxidation treatment is carried out for a holding time of 1 to 6 hours.
[0016] Preferably, the heating rate of the pre-oxidation treatment is 0.5-5°C / min.
[0017] Preferably, the softening point of the asphalt is ≥240°C;
[0018] Preferably, the asphalt includes at least one of natural asphalt, petroleum asphalt, shale asphalt and coal asphalt.
[0019] Preferably, the temperature of the high-temperature carbonization is 1300-1600° C., and the holding time of the high-temperature carbonization is 2-6 hours;
[0020] Preferably, the heating rate of the high temperature carbonization is 0.5-20° C. / min.
[0021] Preferably, the high temperature carbonization is carried out in a non-oxidizing atmosphere;
[0022] Preferably, the gas used for the non-oxidizing atmosphere includes at least one of argon, nitrogen, hydrogen, ammonia and helium.
[0023] The present invention also provides a hard carbon material, which is prepared by the method for preparing the hard carbon material as described above.
[0024] Preferably, the hard carbon material has a first discharge specific capacity of ≥300 mAh / g and a first efficiency of ≥90% at a current density of 30 mA / g;
[0025] Preferably, the hard carbon material has a first discharge specific capacity of ≥310 mAh / g and a first efficiency of ≥91% at a current density of 30 mA / g.
[0026] The present invention also provides a negative electrode material, comprising the hard carbon material as described above.
[0027] The present invention also provides a sodium ion battery, comprising a negative electrode mainly made of the negative electrode material as described above.
[0028] Compared with the prior art, the present invention has the following beneficial effects:
[0029] (1) The method for preparing the hard carbon material provided by the present invention improves the initial efficiency and charge-discharge capacity of the hard carbon material by pre-oxidizing the asphalt at a specific temperature and a specific pressure and then carbonizing it at a high temperature.
[0030] (2) The method for preparing the hard carbon material provided by the present invention uses asphalt as a hard carbon precursor, which has abundant sources and low costs.
[0031] (3) The method for preparing the hard carbon material provided by the present invention has a simple process, a short flow, and is easy to mass produce. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0033] Figure 1 This is a graph showing the electrochemical performance test results of the hard carbon material obtained in Example 3 provided by the present invention.
[0034] Figure 2 This is a graph showing the electrochemical performance test results of the hard carbon material prepared in Comparative Example 1 provided by the present invention. DETAILED DESCRIPTION
[0035] The technical scheme of the present invention will be clearly and completely described below in conjunction with the accompanying drawings and specific embodiments, but it will be understood by those skilled in the art that the following described embodiments are part of embodiments of the present invention, rather than all embodiments, and are only used to illustrate the present invention, and should not be considered as limiting the scope of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work are within the scope of protection of the present invention. If specific conditions are not specified in the embodiments, they are carried out according to normal conditions or conditions recommended by the manufacturer. If the manufacturer is not specified in the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0036] In a first aspect, the present invention provides a method for preparing a hard carbon material that can be used as a negative electrode material for a sodium ion battery, comprising the following steps:
[0037] The asphalt is pre-oxidized at a pressure of 5 to 50 bar and a temperature of 250 to 400° C. to obtain a pre-oxidized asphalt material.
[0038] The pressure of the pre-oxidation treatment may be any point value including but not limited to 10 bar, 15 bar, 20 bar, 25 bar, 30 bar, 35 bar, 40 bar, 45 bar, or a range value between any two of them.
[0039] The temperature of the pre-oxidation treatment may be any one of 280° C., 300° C., 320° C., 350° C., and 380° C., or a range of any two thereof.
[0040] The purpose of the pre-oxidation treatment is to oxidatively cross-link and thereby obtain hard carbon. Without the pre-oxidation treatment, soft carbon is obtained.
[0041] The pre-oxidized asphalt material is carbonized at high temperature to obtain the hard carbon material.
[0042] The present invention uses asphalt as a hard carbon precursor, adopts an air thermal pre-oxidation process, and then high-temperature carbonization to prepare a hard carbon negative electrode material. When used as a negative electrode material for sodium ion batteries, it exhibits high initial efficiency and high capacity.
[0043] The air thermal pre-oxidation process used in the present invention is similar to the hydrothermal and solvent thermal processes. The present invention uses high-pressure air instead of water and solvents to oxidize asphalt under supercritical conditions, which is superior to conventional air oxidation processes and oxidant processes. The hard carbon material prepared by this process has the advantages of high initial efficiency and high charge and discharge capacity, and can be used as a negative electrode material for sodium ion batteries.
[0044] Furthermore, the hard carbon precursor-asphalt used in the present invention is abundant in source and low in cost.
[0045] In addition, the preparation method of the hard carbon material provided by the present invention has the advantages of simple process, short flow, and easy batch production.
[0046] In some specific embodiments of the present invention, the pre-oxidation treatment is carried out in a reactor.
[0047] Preferably, the holding time of the pre-oxidation treatment is 1 to 6 hours, including but not limited to any one of 2 hours, 3 hours, 4 hours, and 5 hours, or a range between any two of them.
[0048] Preferably, the heating rate of the pre-oxidation treatment is 0.5-5°C / min, including but not limited to any point value of 1°C / min, 2°C / min, 3°C / min, 4°C / min or a range value between any two of them.
[0049] That is, the heating rate to the pre-oxidation temperature of 250 to 400° C. is 0.5 to 5° C. / min.
[0050] Preferably, the softening point of the asphalt is ≥240°C, including but not limited to any one of 250°C, 260°C, 270°C, 280°C, 290°C, 300°C, 310°C, 330°C, 350°C or a range between any two of them.
[0051] Preferably, the asphalt includes at least one of natural asphalt, petroleum asphalt, shale asphalt and coal asphalt.
[0052] In some specific embodiments of the present invention, natural asphalt, petroleum asphalt, shale asphalt or coal asphalt with a softening point ≥ 240°C is used.
[0053] Preferably, the temperature of the high temperature carbonization is 1300-1600°C, including but not limited to any one of 1350°C, 1400°C, 1450°C, 1500°C, 1550°C or a range between any two of them.
[0054] The heat preservation time of the high temperature carbonization is 2 to 6 hours, including but not limited to any one of 3 hours, 4 hours, and 5 hours, or a range between any two of them.
[0055] Preferably, the heating rate of the high temperature carbonization is 0.5-20°C / min, including but not limited to any one of 3°C / min, 5°C / min, 8°C / min, 10°C / min, 12°C / min, 15°C / min, 18°C / min or a range between any two of them.
[0056] That is, the heating rate to the high temperature carbonization temperature of 1300 to 1600° C. is 0.5 to 20° C. / min.
[0057] Preferably, the high-temperature carbonization is performed in a non-oxidizing atmosphere, such as a reducing atmosphere or an inert atmosphere.
[0058] Preferably, the gas used for the non-oxidizing atmosphere includes at least one of argon, nitrogen, hydrogen, ammonia and helium.
[0059] In a second aspect, the present invention provides a hard carbon material, which is prepared by the method for preparing the hard carbon material as described above.
[0060] The hard carbon material provided by the present invention has the advantages of low cost, high initial efficiency and high charge and discharge capacity.
[0061] Preferably, the first discharge specific capacity of the hard carbon material at a current density of 30 mA / g is ≥300 mAh / g, including but not limited to any one of 303 mAh / g, 305 mAh / g, 307 mAh / g, 310 mAh / g, 315 mAh / g, 318 mAh / g, 320 mAh / g, and 330 mAh / g, or a range between any two of them.
[0062] The first efficiency of the hard carbon material at a current density of 30 mA / g is ≥90%, including but not limited to any one of 90.5%, 91%, 91.5%, 92%, 93% or a range between any two of them.
[0063] Preferably, the hard carbon material has a first discharge specific capacity of ≥310 mAh / g and a first efficiency of ≥91% at a current density of 30 mA / g.
[0064] In a third aspect, the present invention provides a negative electrode material, comprising the hard carbon material as described above.
[0065] In a fourth aspect, the present invention provides a sodium ion battery, comprising a negative electrode mainly made of the negative electrode material as described above.
[0066] That is, the sodium ion battery includes a negative electrode (negative electrode plate), and the negative electrode is mainly made of the negative electrode material as described above.
[0067] The sodium ion battery has excellent electrochemical performance, especially high initial efficiency and high charge and discharge capacity, high sodium storage efficiency, and low preparation cost.
[0068] The embodiments of the present invention will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. If no specific conditions are specified in the examples, the conditions are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be obtained commercially.
[0069] The electrochemical performance test standards and test methods of the hard carbon materials prepared in the following embodiments and comparative examples are as follows: the hard carbon materials prepared in the embodiments and comparative examples are used as the negative electrode material, the positive electrode is sodium metal, the electrolyte is 1 mol NaFP6 dissolved in EC:DMC (1:1), and the diaphragm is glass fiber (GF / A).
[0070] Example 1
[0071] The method for preparing the hard carbon material provided in this embodiment comprises the following steps:
[0072] 500 g of petroleum asphalt with a softening point of 250° C. was placed in a high-temperature reactor, heated to 300° C. at a heating rate of 2° C. / min, and kept warm for 3 hours at an air pressure of 25 bar to perform pre-oxidation treatment to obtain a pre-oxidized asphalt material.
[0073] Then, the pre-oxidized asphalt material was placed in a tubular furnace in an Ar atmosphere, heated to 1400° C. at a heating rate of 5° C. / min and kept at that temperature for 3 hours for high-temperature carbonization. After cooling to room temperature, the hard carbon material was obtained.
[0074] After testing, the hard carbon material prepared in this example has a first discharge specific capacity of 315.6 mAh / g at a current density of 30 mA / g, and a first efficiency of 90.56%.
[0075] Example 2
[0076] The method for preparing the hard carbon material provided in this embodiment comprises the following steps:
[0077] 500 g of petroleum asphalt with a softening point of 270° C. was placed in a high-temperature reactor, heated to 305° C. at a heating rate of 2.5° C. / min, and kept warm for 2 hours at an air pressure of 15 bar to perform pre-oxidation treatment to obtain a pre-oxidized asphalt material.
[0078] Then the pre-oxidized asphalt material was placed in a tubular furnace in an Ar atmosphere, heated to 1450° C. at a heating rate of 2° C. / min and kept at that temperature for 2 hours for high temperature carbonization. After cooling to room temperature, the hard carbon material was obtained.
[0079] According to the test, the hard carbon material prepared in this example has a first discharge specific capacity of 318.3 mAh / g at a current density of 30 mA / g, and a first efficiency of 91.02%.
[0080] Example 3
[0081] The method for preparing the hard carbon material provided in this embodiment comprises the following steps:
[0082] 500 g of petroleum asphalt with a softening point of 280° C. was placed in a high-temperature reactor, heated to 325° C. at a heating rate of 0.5° C. / min, and kept warm for 2 hours at an air pressure of 25 bar to perform pre-oxidation treatment to obtain a pre-oxidized asphalt material.
[0083] Then the pre-oxidized asphalt material was placed in a tubular furnace in a N2 atmosphere, heated to 1400°C at a heating rate of 1°C / min and kept at that temperature for 4 hours for high temperature carbonization. After cooling to room temperature, the hard carbon material was obtained.
[0084] After testing, the hard carbon material prepared in this example has a first discharge specific capacity of 320.6 mAh / g at a current density of 30 mA / g, and a first efficiency of 91.62%.
[0085] like Figure 1 Shown is a graph showing the electrochemical performance test results of the hard carbon material prepared in this example.
[0086] Example 4
[0087] The method for preparing the hard carbon material provided in this embodiment comprises the following steps:
[0088] 500 g of coal tar pitch with a softening point of 270° C. was placed in a high-temperature reactor, heated to 320° C. at a heating rate of 2.5° C. / min, and kept warm for 4 hours at an air pressure of 15 bar to perform pre-oxidation treatment to obtain a pre-oxidized asphalt material.
[0089] Then the pre-oxidized asphalt material was placed in a tubular furnace in a He atmosphere, heated to 1550° C. at a heating rate of 0.5° C. / min and kept at that temperature for 3 hours for high temperature carbonization. After cooling to room temperature, the hard carbon material was obtained.
[0090] According to the test, the hard carbon material prepared in this embodiment has a first discharge specific capacity of 308.8 mAh / g at a current density of 30 mA / g, and a first efficiency of 90.71%.
[0091] Example 5
[0092] The method for preparing the hard carbon material provided in this embodiment comprises the following steps:
[0093] 500 g of coal tar pitch with a softening point of 280° C. was placed in a high-temperature reactor, heated to 350° C. at a heating rate of 1.5° C. / min, and kept warm for 1 hour at an air pressure of 5 bar to perform pre-oxidation treatment to obtain a pre-oxidized asphalt material.
[0094] Then, the pre-oxidized asphalt material was placed in a tubular furnace in an Ar atmosphere, heated to 1450° C. at a heating rate of 1° C. / min and kept at that temperature for 3 hours for high-temperature carbonization. After cooling to room temperature, the hard carbon material was obtained.
[0095] After testing, the hard carbon material prepared in this example has a first discharge specific capacity of 309.5 mAh / g at a current density of 30 mA / g, and a first efficiency of 91.14%.
[0096] Example 6
[0097] The method for preparing the hard carbon material provided in this embodiment comprises the following steps:
[0098] 500 g of coal tar pitch with a softening point of 300° C. was placed in a high-temperature reactor, heated to 300° C. at a heating rate of 5° C. / min, and kept warm for 2 hours at an air pressure of 50 bar to perform pre-oxidation treatment to obtain a pre-oxidized asphalt material.
[0099] Then the pre-oxidized asphalt material was placed in a tubular furnace in an Ar atmosphere, heated to 1550° C. at a heating rate of 2.5° C. / min and kept at that temperature for 2 hours for high temperature carbonization. After cooling to room temperature, the hard carbon material was obtained.
[0100] After testing, the hard carbon material prepared in this example has a first discharge specific capacity of 307.2 mAh / g at a current density of 30 mA / g, and a first efficiency of 91.07%.
[0101] Example 7
[0102] The method for preparing the hard carbon material provided in this embodiment comprises the following steps:
[0103] 500 g of petroleum asphalt with a softening point of 350° C. was placed in a high-temperature reactor, heated to 350° C. at a heating rate of 1.5° C. / min, and kept warm for 2 hours at an air pressure of 30 bar to perform pre-oxidation treatment to obtain a pre-oxidized asphalt material.
[0104] Then the pre-oxidized asphalt material was placed in a tubular furnace in a H2-Ar atmosphere, heated to 1400°C at a heating rate of 0.5°C / min and kept at that temperature for 3 hours for high temperature carbonization. After cooling to room temperature, the hard carbon material was obtained.
[0105] After testing, the hard carbon material prepared in this example has a first discharge specific capacity of 317.7 mAh / g at a current density of 30 mA / g, and a first efficiency of 91.03%.
[0106] Example 8
[0107] The method for preparing the hard carbon material provided in this embodiment comprises the following steps:
[0108] 500 g of petroleum asphalt with a softening point of 300° C. was placed in a high-temperature reactor, heated to 300° C. at a heating rate of 0.5° C. / min, and kept warm for 4 hours at an air pressure of 50 bar to perform pre-oxidation treatment to obtain a pre-oxidized asphalt material.
[0109] Then the pre-oxidized asphalt material was placed in a tubular furnace in an Ar atmosphere, heated to 1450° C. at a heating rate of 1.5° C. / min and kept at that temperature for 3 hours for high temperature carbonization. After cooling to room temperature, the hard carbon material was obtained.
[0110] After testing, the hard carbon material prepared in this example has a first discharge specific capacity of 316.8 mAh / g at a current density of 30 mA / g, and a first efficiency of 91.24%.
[0111] Comparative Example 1
[0112] The preparation method of the hard carbon material provided in this comparative example is basically the same as that of Example 3, with the only difference being that the air pressure during the pre-oxidation treatment is replaced with 1 bar, that is, the pre-oxidation treatment is carried out under normal pressure.
[0113] After testing, the hard carbon material prepared in this comparative example has a first discharge specific capacity of 293.5 mAh / g at a current density of 30 mA / g, and a first efficiency of 90.3%.
[0114] like Figure 2 Shown is a graph showing the electrochemical performance test results of the hard carbon material prepared in Comparative Example 1.
[0115] Comparative Example 2
[0116] The preparation method of the hard carbon material provided in this comparative example is basically the same as that of Example 3, except that the temperature during the pre-oxidation treatment is replaced with 200°C.
[0117] After testing, the hard carbon material prepared in this comparative example has a first discharge specific capacity of 237.3 mAh / g at a current density of 30 mA / g, and a first efficiency of 76.3%.
[0118] Comparative Example 3
[0119] The preparation method of the hard carbon material provided in this comparative example is basically the same as that in Example 3, with the only difference being that no pre-oxidation treatment is performed, that is: 500 g of petroleum asphalt with a softening point of 280°C is directly placed in a tubular furnace in a N2 atmosphere, and the temperature is increased to 1400°C at a heating rate of 1°C / min and kept for 4 hours for high-temperature carbonization.
[0120] After testing, the hard carbon material prepared in this comparative example has a first discharge specific capacity of 212.4 mAh / g at a current density of 30 mA / g, and a first efficiency of 63.9%.
[0121] By comparing the above electrochemical performance test results, it can be seen that the hard carbon materials prepared in each embodiment have a higher first efficiency and a higher first discharge specific capacity. In particular, in Example 3, the first discharge specific capacity is as high as 320.6 mAh / g, and the first efficiency is as high as 91.62%. However, after changing the pre-oxidation treatment steps and parameters of Comparative Examples 1 to Comparative Examples 3, the first efficiency and first discharge specific capacity are significantly reduced.
[0122] In summary, the preparation method of the hard carbon material provided by the present invention can improve the initial efficiency and charge and discharge capacity of the hard carbon material, and the hard carbon material prepared by the method can be used as a negative electrode material for sodium ion batteries.
[0123] Although the present invention has been illustrated and described with specific embodiments, it should be appreciated that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Those skilled in the art should understand that the technical solutions described in the above embodiments may be modified, or some or all of the technical features thereof may be replaced by equivalents without departing from the spirit and scope of the present invention. However, these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention. Therefore, this means that all such replacements and modifications within the scope of the present invention are included in the appended claims.
Claims
1. A method for preparing a hard carbon material, characterized in that: The steps include: Using air thermal preoxidation process, the asphalt is preoxidized at a pressure of 5-50 bar and a temperature of 250-400°C to obtain preoxidized asphalt material; The pre-oxidized asphalt material is carbonized at high temperature to obtain the hard carbon material; The holding time of the pre-oxidation treatment is 1 to 6 hours; The heating rate of the pre-oxidation treatment is 0.5-5°C / min; The hard carbon material has a first discharge specific capacity of ≥300 mAh / g at a current density of 30 mA / g, and a first efficiency of ≥90%.
2. The method for preparing a hard carbon material according to claim 1, characterized in that: The softening point of the asphalt is ≥240°C.
3. The method for preparing a hard carbon material according to claim 1, characterized in that: The asphalt includes at least one of natural asphalt, petroleum asphalt, shale asphalt and coal asphalt.
4. The method for preparing a hard carbon material according to claim 1, characterized in that: The temperature of the high-temperature carbonization is 1300-1600° C., and the insulation time of the high-temperature carbonization is 2-6 hours.
5. The method for preparing a hard carbon material according to claim 1, characterized in that: The heating rate of the high temperature carbonization is 0.5-20°C / min.
6. The method for preparing a hard carbon material according to claim 1, characterized in that: The high temperature carbonization is performed in a non-oxidizing atmosphere.
7. The method for preparing a hard carbon material according to claim 6, characterized in that: The gas used for the non-oxidizing atmosphere includes at least one of argon, nitrogen, hydrogen, ammonia and helium.
8. A hard carbon material, characterized in that: The hard carbon material is prepared by the method for preparing the hard carbon material according to any one of claims 1 to 7.
9. The hard carbon material according to claim 8, characterized in that The hard carbon material has a first discharge specific capacity of ≥310 mAh / g at a current density of 30 mA / g, and a first efficiency of ≥91%.
10. A negative electrode material, characterized in that: Comprising the hard carbon material as described in any one of claims 8 to 9.
11. A sodium ion battery, characterized in that: The invention comprises a negative electrode mainly made of the negative electrode material as claimed in claim 10.
Citation Information
Patent Citations
Asphalt-based negative electrode material for sodium ion battery and preparation method and application thereof
CN109148883A
Method for preparing high-performance asphalt-based carbon fiber through rapid pre-oxidation
CN114790592A